Exploring the Nexus of Self-Efficacy, Family Support, and Educational Environment on University Pursuit Motivation - Muhammad Safri; Eka Hendi Andriansyah; Mohamad Arif Rafsanjani; Wapodo Tjipto Subroto (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to investigate the correlation between a student's self-efficacy, family environment, and school environment, and their inclination towards pursuing higher education post high school. The research methodology employed is associative research utilising a quantitative technique. The study included a population of 280 students from all State Senior High Schools in the Menganti Subdistrict. The sampling strategy employed was purposive sampling to select class 12 state senior high schools in the city of Menganti as the sample, consisting of 198 students. Data collecting methods involve the use of questionnaires and are analysed by multiple regression with the assistance of the SPSS software. The results of the F test indicate a significant value of 0.000 0.05 and a calculated F value of 39.128 F table 2.26, suggesting that the independent variable has a significant influence on the dependent variable. The t-test results indicate that the tcount value is 3.317, exceeding the t table value of 1.65259 with a significance level of 0.001 0.05 for the self-efficacy variable. Additionally, the t count value of 4.359 surpasses the t table value of 1.65259 with a significance level of 0.000 0.05 for the family environment variable. The t count value is 0.526, which is less than the t table value of 1.65259, resulting in a significance value of 0.599, which is greater than 0.05 for the school environment variable. The T-test results indicate that each independent variable has a partial impact on the dependent variable.